2017
DOI: 10.1002/ejp.1019
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and distribution of body fat can influence sensory detection and pain sensitivity

Abstract: This study provided evidence that body mass index and distribution of body fat can influence sensory detection and pain sensitivity. Obese individuals were more sensitive than normal range body mass index individuals to pressure pain but not to thermal pain. Pain response varied according to subcutaneous body fat at different body sites. These findings strengthen arguments that weight loss should be a significant aspect of a pain management programme for obese pain patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 39 publications
4
45
2
1
Order By: Relevance
“…However, we found no differences in pain threshold for any of the noxious stimuli used (i.e. pressure, contact heat or cold pressor), and this is not consistent with previous studies by ourselves or others that have found that women have lower pain thresholds than men [16,21]. We calculated sample size based on detecting a relationship between age and pain sensitivity response rather than between men and women and this might explain the discrepancy.…”
Section: Sex/gender-related Pain Sensitivity Responsecontrasting
confidence: 82%
See 1 more Smart Citation
“…However, we found no differences in pain threshold for any of the noxious stimuli used (i.e. pressure, contact heat or cold pressor), and this is not consistent with previous studies by ourselves or others that have found that women have lower pain thresholds than men [16,21]. We calculated sample size based on detecting a relationship between age and pain sensitivity response rather than between men and women and this might explain the discrepancy.…”
Section: Sex/gender-related Pain Sensitivity Responsecontrasting
confidence: 82%
“…The sample size was calculated for heat pain threshold as a dependent variable and age as the independent variable using an online software calculator (https://www.ai-therapy.com/psychology-statistics/sample-size-calculator). A sample size calculation was conducted using alpha set at 0.05, beta set at 0.90 and a correlation coefficient of 0.33 based on a previous study [16] resulting in a target of 52 participants. Therefore, a total of 56 participants were recruited in anticipation of some participants may drop out during the experimental procedures.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…55 Interestingly, BMI was associated with increased pain facilitation and reduced pain inhibition for TMD cases when tested over the face, despite no between-group differences for mean BMI or across BMI categories. It has been recently suggested that BMI may influence pain sensitivity, with obese pain-free participants presenting with lower PPT compared to normal or overweight participants, 61 and there is also evidence that individuals who report greater physical activity levels present with reduced TSP and greater CPM responses. 62 BMI relationship with EPM is an underdeveloped field of research, and to the best of our knowledge, no study with a specific focus on such relationship has been reported to date.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…To date, we are not aware of any studies that have examined lipid levels in relation to peripheral and central sensitivity, although fat distribution has been shown to influence pressure pain threshold. A recent study evaluating pain sensitivity among normal weight, overweight and obese individuals reported that pressure pain threshold was significantly lower in overweight and obese compared to normal weight individuals whereas thermal pain thresholds were not significantly different between groups (Tashani, Astita, Sharp, & Johnson, 2017). Further research regarding how triacylglycerol levels, specifically TAG 50:2, may influence pain sensitivity are needed, with careful attention to controlling for body mass index and fat distribution in mechanical and deep tissue pain sensitivity assessments.…”
Section: Discussionmentioning
confidence: 99%